Using Pecha Kucha Presentation in Teaching English Speaking: A Pre-Experimental Study on Islamic Senior High School Students - Wahyudi, Dedy; Rafli, M. Akbar; Wouda, Ferdinand H.P. (Al-Manar, 2024)
The present study aimed at examining whether there is a significant difference in students’ English speaking ability before and after being taught by using Pecha Kucha Presentation. This study employed a pre-experimental design which was one-group pretest- posttest design. The population in this study was 285 students at the tenth grade of MAN 3 Pekanbaru (Islamic Senior High School). One class was taken as the sample comprising 35 students. This study utilized pretest, treatment, and posttest for gathering the research data. Then, the collected data were statistically analyzed using a paired sample T-test on SPSS version 23. With reference to the analysis, the results showed a significant difference in students’ English speaking ability before and after being taught by using Pecha Kucha Presentation. To conclude, the use of Pecha Kucha Presentation influences the students’ English speaking ability significantly.